2011
DOI: 10.17159/2413-3051/2011/v22i2a3214
|View full text |Cite
|
Sign up to set email alerts
|

The effect of open sun and indoor forced convection on heat transfer coefficients for the drying of papad

Abstract: In this research paper, a simulation study has been carried out for the determination of convective heat transfer coefficients of papad under open sun drying and indoor forced convection drying modes. Experimental data obtained from open sun and indoor forced convection drying modes for papad were used to determine the values of the constants (C and n) in Nusselt number expression by using linear regression analysis, and consequently convective heat transfer coefficients were evaluated. The average values of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 8 publications
2
10
0
Order By: Relevance
“…So, it has been reported that the drying kinetics of asparagus is highly dependent on the mass is taken into consideration. The researchers (Jayashree et al, 2014;Karna & Koo, 2017;Kumar et al, 2011;Ünal, Alpsoy, & Ayhan, 2013) reported results were in closer agreements with our results of the study. They studied that convective heat transfer has been decreased with the increasing mass of the samples dried.…”
Section: Re Sults and Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…So, it has been reported that the drying kinetics of asparagus is highly dependent on the mass is taken into consideration. The researchers (Jayashree et al, 2014;Karna & Koo, 2017;Kumar et al, 2011;Ünal, Alpsoy, & Ayhan, 2013) reported results were in closer agreements with our results of the study. They studied that convective heat transfer has been decreased with the increasing mass of the samples dried.…”
Section: Re Sults and Discussionsupporting
confidence: 92%
“…According to Karna & Koo, 2017;Khoukhi & Maruyama, 2006;Kong, Lin, & Li, 2013; they reported the 26.25 W/m 2 for convective heat transfer coefficient of asparagus sample under the sun-drying condition. Other studies (Kumar, Khatak, Sahdev, & Prakash, 2011;Kumar, Sansaniwal, & Khatak, 2015;Kumar & Tiwari, 2009) have been reported that drying rate under the hybrid dryer was greater than sun-drying with the efficiency of 15% during the summer season. Modified Henderson and Pabis were reported to be best suited to describe the drying behavior of Asparagus (Lu, Yu, & Ding, 2003).…”
mentioning
confidence: 84%
“…This is due to decrease in total moisture contents removal with the drying day progression from the 1 st to the 3 rd day. The trends of the evaluated results for the convective heat transfer coefficients are observed in accordance with those reported for khoa drying under greenhouse and open sun drying modes by Kumar et al [19]. The average value of convective heat transfer coefficient is observed to decrease by 28.35% for the given drying days.…”
Section: Resultssupporting
confidence: 88%
“…The convective heat transfer coefficient for evaporation under forced convection can be determined by using the following relations [19,20]:…”
Section: Thermal Modelingmentioning
confidence: 99%
“…More the coefficient of convective heat transfer more will be the moisture removing rate and vice versa as illustrated in Figure 5. Forced convection drying system has been reported to be best suitable for faster drying as the value of coefficient of convective heat transfer associated with them is more than the natural convection drying [28]. From Figure 5, it has been observed that the values of convective heat transfer coefficient ( c h ) decreases with the progression of drying days (i.e.…”
Section: Resultsmentioning
confidence: 99%